The Influence of Hot Forming and Heat Treatment on the Mechanical Properties of 9Ni Steel Plate for Small Pressure Storage Tanks - Zhang Jun, Shen Yan, Yu Xiong (Teshugang)
Taking 9Ni steel plate as the object of analysis， the different heat treatment processes of 9Ni steel plate in the head manufacturing process were simulated in the laboratory， and the properties of the test plate in hot-formed state，hot-formed state+QT state，hot-formed state+NNT state and the corresponding post-welded stress relieving state were investigated respectively.The results show that： 20 mm thick 9Ni steel test plate after 930 ℃ high-temperature hot forming，the base material structure was completely destroyed，its reverse austenite basically disappeared，the yield strength decreased by 100 MPa，and the maximum impact energy absorbed at -196 ℃ was only 10 J，it must be re-heat treated to restore the mechanical properties. After hot forming， the mechanical properties of the test plate were restored using the NNT process. Compared with the QT recovery process， the -196 ℃ impact absorption energy， room temperature yield strength， and room temperature tensile strength were significantly lower. The reason for this was that the NNT process test plate contained significantly lower content of inverted austenite than the QT process test plate. Therefore， the mechanical properties restored by QT process were good and stable. After the elongation cold deformation of 2.5%-7.5%， when the aging treatment temperature reached 250 ℃， the average aging sensitivity coefficient of 20 ℃ and-196 ℃ shock absorption energy was 0.62% to 10%， and the aging sensitivity of the base material was low；When the aging treatment temperature reached 540 ℃， the average aging sensitivity coefficient was 13.93% to 30.63%. Although the aging sensitivity of the base material slightly increased， the impact absorption energy showed a small decrease， but all were greater than 180 J. The surplus of impact absorption energy of the base material was still relatively large.